The importance of public investment for reducing rural poverty in middle-income countries: the case of Thailand - Fan, Shenggen; Jitsuchon, Somchai; Methakunnavut, Nuntaporn (International Food Policy Research Institute, 2004)
This study estimates the impacts of different types of government expenditure on agricultural growth and rural poverty in Thailand. The results show that, despite Thailand's middle-income status, public investments in agricultural R&D, irrigation, rural education, and infrastructure (including roads and electricity), still have positive marginal impacts on agricultural productivity growth and rural poverty reduction. Additional government spending on agricultural research and development improves agricultural productivity the most and has the second largest impact on rural poverty reduction. Investments in rural electrification reduce poverty the most and have the second largest growth impact. These two investments dominate all others and are win-win for growth and poverty reduction. Road expenditure has the third largest impact on rural poverty reduction, but only a modest and statistically insignificant impact on agricultural productivity. Government spending on rural education has only the fourth largest impact on poverty, but a significant economic impact through improved agricultural productivity. Irrigation investment has the smallest impact on both rural poverty reduction and productivity growth in agriculture. Additional investments in the Northeast region contribute more to reducing poverty than investments in other regions. This is because most of the poor are now concentrated in the Northeast and it has suffered from under investment in the past. The poverty reducing impacts of infrastructure investments, such as electricity and roads, are particularly high in this region. The growth impacts of many investments are also greatest in the Northeast than in other regions, hence there is no evident tradeoff between investments for growth and investments for poverty reduction. Thailand is a middle-income country and it is insightful to compare these results with similar studies undertaken in low-income countries like India, China, and Uganda. Some of the results are similar, for example, the high returns to public investments in agricultural research and some kinds of rural infrastructure arise in most countries because of the inherent market failures associated with these types of public goods. But others results are different. For example, the returns to public investment in education in Thailand are quite low, partly because of increasing private investment but also the inappropriate composition of much public spending on education. Within infrastructure, results from low-income countries often show higher returns to road investments than telecommunications and electricity. But in the case of Thailand, it is investment in electricity that shows the highest return. Thailand has invested heavily in rural roads and a dense road network has already been built, suggesting that additional investment may yield diminishing returns. Also, there has been significant investment by the private sector in rural telecommunication, leading to a much-reduced role for the public sector. This situation differs from many low-income countries, especially in Africa, where the private sector is still embryonic and the public sector must play a dominant investment role for the foreseeable future.